2017
DOI: 10.1093/neuros/nyx570
|View full text |Cite
|
Sign up to set email alerts
|

Adult Craniopharyngioma: Case Series, Systematic Review, and Meta-Analysis

Abstract: This is the first and largest systematic review focusing on the rate of recurrence in adult craniopharyngioma. Although the rates of recurrence are favoring GTR, difference in risk of recurrence did not reach significance. This study provides guidance to clinicians and directions for future research with the need to stratify outcomes per treatment modalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
2
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 63 publications
2
47
2
4
Order By: Relevance
“…Examination of the visual function is an important element in the diagnosis, monitoring, and prognosis for craniopharyngiomas. Visual decline is one of the most freq u e n t i n i t i a l m a n i f e s t a t i o n s i n p a t i e n t s w i t h craniopharyngiomas [150], accounting for two-thirds of clinical presentation in adult-onset tumors [31]. As many as 80% of patients have a visual deficit at the preoperative ophthalmologic evaluation [159,183].…”
Section: Evidencementioning
confidence: 99%
“…Examination of the visual function is an important element in the diagnosis, monitoring, and prognosis for craniopharyngiomas. Visual decline is one of the most freq u e n t i n i t i a l m a n i f e s t a t i o n s i n p a t i e n t s w i t h craniopharyngiomas [150], accounting for two-thirds of clinical presentation in adult-onset tumors [31]. As many as 80% of patients have a visual deficit at the preoperative ophthalmologic evaluation [159,183].…”
Section: Evidencementioning
confidence: 99%
“…15 Post-operatively, in our patient, visual impairment decreased and hypothalamic dysfunction was not observed. In their meta-analysis, Dandurand et al 7 compared the gross total resection of CPs with subtotal resection followed by adjuvant radiotherapy and found that the lowest recurrence rate was achieved with gross total resection. In our patient, gross total resection of CP was performed, and no recurrence was observed at the first 6-month follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…They account for 2%-5% of intracranial tumour primers, with an incidence of 0.5-2.0 billion per year. 7 The bimodal age distribution peaks between 0 and 19 and 40 and 79 years of age. 20 While complete improvement can be achieved with radical resection of CP, high recurrence rates have been reported for partial resection.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the tremendous progress made in diagnostic and surgical methodologies, however, the optimal treatment for these challenging lesions remains controversial. 12,17,30,32 The debate centers around what is the best surgical strategy, either radical tumor resection or limited debulking plus adjuvant therapy. 29,31,33,34 Cushing went through the same dilemma, as shown by the continuous evolution of his surgical techniques and philosophy throughout his career.…”
Section: Continuing Controversy Over Cp Treatment: Lessons Learned Frmentioning
confidence: 99%